2001
DOI: 10.1136/jcp.54.5.381
|View full text |Cite
|
Sign up to set email alerts
|

Retain or sacrifice the posterior cruciate ligament in total knee arthroplasty? A histopathological study of the cruciate ligament in osteoarthritic and rheumatoid disease

Abstract: Background-The decision whether to retain or resect the posterior cruciate ligament in total knee arthroplasty is at present determined clinically by preoperative radiological variables focusing upon the amount of joint destruction, and subsequent soft tissue contractures. However, these variables give only indirect information on the histological integrity and proprioceptive properties of the posterior cruciate ligament. Methods-Twenty posterior cruciate ligaments, obtained during total knee arthroplasty, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 17 publications
5
44
0
2
Order By: Relevance
“…In these tests, it was found that the mucoid degeneration of the ligament was related to the stratification and destruction of collagen fibres. Similar changes have been described previously by Nelissen and Hogendorn [13] in 20 PCL samples taken during TKA. They report mucoid degeneration and abnormal course, with disturbances in the spatial structure of the collagen fibres.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In these tests, it was found that the mucoid degeneration of the ligament was related to the stratification and destruction of collagen fibres. Similar changes have been described previously by Nelissen and Hogendorn [13] in 20 PCL samples taken during TKA. They report mucoid degeneration and abnormal course, with disturbances in the spatial structure of the collagen fibres.…”
Section: Discussionsupporting
confidence: 89%
“…They show nerve endings to be present in anterior cruciate ligament and PCL preparations, while also observing a reduction in the number of mechanoreceptors in degenerative diseases of the knee. The presence of proprioceptors in the PCL has been demonstrated by a number of authors using various staining methods [9,13]. Barrett et al [4] and Skinner et al [19] describe a weakening of proprioception to be associated with age and with greater degenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 Mucoid degeneration of the fibres was frequently seen. Another study revealed that degeneration or rupture of the anterior cruciate ligament strongly reflected the histological state of the PCL.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, although most PCLs have an intact neural structure, extensive mucoid degeneration and irregular fibre pattern are noted. 32 Radiological grading of osteoarthritis matches the functional state of the PCL; therefore, PCL-retaining prosthesis should not be used in patients with osteoarthritis of greater than grade-5 severity. 32 The mechanical property of PCL as a physical restraint to posterior translation of the tibia is well established.…”
Section: Discussionmentioning
confidence: 99%